Instytut Polski w Sofii - Galina Georgiewa; Radostina Petrowa (Postscriptum Polonistyczne)
Polish Institute in Sofia (former Polish Cultural and Information Centre) is one of the oldest cultural institutions of this type in the Balkans and the most important centre for promotion of Polish culture in Bulgaria. For many years it has been supporting PolishBulgarian contacts in the field of science and culture arranging courses of Polish language for Bulgarians, cooperating with Bulgarian universities, Slavic Studies Institutes and other cultural institutions. Paper presents history of the Institute, its activities in different fields (promotion of Polish literature, music, arts, science etc.) and its contribution to relations between the two countries.